Contextual Market Basket Analysis during Covid-19 - Gisela Christy Mooy; Sani M Isa (Journal of Social Science, 2023)
One form of Data Mining application to analyze Market Basket Analysis. Market Basket Analysis helps identify buying patterns formed from concurrent transactions. One of the problems with Market Basket Analysis is that customer needs vary according to season and time of day, especially during this covid-19 season. For this purpose, by using the Artificial Neural Network (ANN) Approach that is connected to Market Basket Analysis, it can analyze and compare purchasing patterns and can identify rules that were formed before and after covid-19; several rule changes were found due to changes in people's behavior patterns.